Surface modifying of nanocrystalline magnetite with aluminum isopropylate - Petranovskaya, A. L.; Usov, D. G.; Abramov, M. V.; Demchenko, Yu. O.; Gorbyk, P. P.; Korduban, O. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2007)
The technique of synthesis of magnetically sensitive nanocomposites on basis of nanocrystalline magnetite modified with aluminum isopropylate in a liquid phase of isopropanol was elaborated. The composition and structure of the nanocomposites obtained was studied by means of IR- Fourier spectroscopy, X-ray diffraction analysis and X-ray photoelectron spectroscopy. Magnetic characteristics of the nanocomposites were investigated using the vibrating-reed magnetometer. The phase of aluminum hydroxide was found to form on the surface of magnetite nanoparticles. It has been shown that the transformation of aluminum hydroxide phase into Al2O3 phase occurs after the sample annealing at 733 К.